2019
DOI: 10.1111/hiv.12750
|View full text |Cite
|
Sign up to set email alerts
|

Population uptake and effectiveness of test‐and‐treat antiretroviral therapy guidelines for preventing the global spread of HIV: an ecological cross‐national analysis

Abstract: Objectives Although the benefits of adopting test‐and‐treat antiretroviral therapy (ART) guidelines that recommend initiation of ART regardless of CD4 cell counts have been demonstrated at the individual level, there is uncertainty about how this translates to the population level. Here, we explored whether adopting ART guidelines recommending earlier treatment initiation improves population ART access and viral suppression and reduces overall disease transmission. Methods Data on ART initiation guidelines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…The Universal HIV "treat all" programme initiated in 2015 by the World Health Organization (WHO) has been effective in increasing the number of infected individual on antiretroviral treatment (ART) worldwide (from 19.4 million in 2016 to 21.7 million people at the end of 2017 [1,2]. A recent HIV impact survey in Tanzania indicated that 1,432,001 people were living with HIV/AIDS and of these, 61% were aware of their HIV status.…”
Section: Introductionmentioning
confidence: 99%
“…The Universal HIV "treat all" programme initiated in 2015 by the World Health Organization (WHO) has been effective in increasing the number of infected individual on antiretroviral treatment (ART) worldwide (from 19.4 million in 2016 to 21.7 million people at the end of 2017 [1,2]. A recent HIV impact survey in Tanzania indicated that 1,432,001 people were living with HIV/AIDS and of these, 61% were aware of their HIV status.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, treatment for PLWH can be initiated on the day of the diagnosis without any impact on ART safety or acceptability [ 13 ]. Same-day ART initiation may shorten the time to virologic suppression, improving retention in care with virologic suppression among patients with early clinical HIV diseases [ 13 , 14 , 16 ]. Indeed, the rapid initiation of ART, including same-day ART, is a World Health Organization recommendation [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is increasingly important to understand differentiated service delivery strategies and outcomes for linkage from different testing modalities as the endorsement of universal test and treat (UTT) has seen global expansion, whereby all PLWH are initiated on ART regardless of disease stage [4]. UTT gradually becoming standard of care has led to increased demand for linkage to ART, including for PLWH who are asymptomatic [5,6 ▪ ,7,8 ▪▪ ,9].…”
Section: Introductionmentioning
confidence: 99%